2007
DOI: 10.4049/jimmunol.178.4.2262
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Sensitize TCRs through Self-MHC-Mediated Src Family Kinase Activation

Abstract: It is unclear whether peptide-MHC class II (pMHC) complexes on distinct types of APCs differ in their capacity to trigger TCRs. In this study, we show that individual cognate pMHC complexes displayed by dendritic cells (DCs), as compared with nonprofessional APCs, are far better in productively triggering Ag-specific TCRs independently of conventional costimulation. As we further show, this is accomplished by the unique ability of DCs to robustly activate the Src family kinases (SFKs) Lck and Fyn in T cells ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…One recent study identified a T cell activation during adhesion to immature dendritic cells in the absence of cognate Ag and attributed this to presentation of self-Ag (37). However, our findings show that the T cell raft capping by unpulsed B cell APCs occurs independently of MHC II, and thus is unlikely to depend on presentation of self-Ag.…”
Section: Discussioncontrasting
confidence: 56%
“…One recent study identified a T cell activation during adhesion to immature dendritic cells in the absence of cognate Ag and attributed this to presentation of self-Ag (37). However, our findings show that the T cell raft capping by unpulsed B cell APCs occurs independently of MHC II, and thus is unlikely to depend on presentation of self-Ag.…”
Section: Discussioncontrasting
confidence: 56%
“…11 In the current study, we observed that the same BMDCs captured both CT and PE (data not shown), indicating that these DCs have an opportunity to process these 2 molecules simultaneously to produce mediators to direct subsequent immune reactions. We also observed that CT upregulated costimulatory molecules CD80 and CD86, and MHC II on DCs, in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 53%
“…DCs capture and process exogenous antigens and transfer the antigenic information to T cells. 11 DCs also produce costimulatory molecules to assist the process of antigen information transfer and T-cell activation. 12 Subsequently, the naive CD4 1 T cells develop to T H 1 or T H 2 cells according to the cytokine milieu.…”
mentioning
confidence: 99%
“…The underlying signals provided by DC despite the absence of high-affinity peptides include MHC-class II-dependent and -independent signals, including Ca 11 -influx and the tyrosine phosphorylation (pY) of z-chain and Src kinases [21][22][23] and, likely, cytokine-derived signals [14].…”
Section: Introductionmentioning
confidence: 99%